PENERAPAN INKUIRI DAN SIKAP ILMIAH SISWA SEKOLAH DASAR SERTA PENGEMBANGANNYA DALAM PEMBELAJARAN PELESTARIAN MAKHLUK HIDUP - Evi Apriana; Samsul Bahri (Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Nature conservation activities aim to keep up plant and animal species to stay sustainable. Efforts to conserve nature can done through education. One strategy that can used by elementary schools is to raise students' awareness of the environment through learning to conserve living things by using a scientific attitude-based inquiry learning model.This study aims to identify the application of inquiry and scientific attitudes of students in learning to conserve living things through needs analysis, documentation studies, and field studies. This study uses a Qualitative Research design, carried out using direct observation methods in class VI students of the semester I who participated in the study of the preservation of living things in three elementary schools in Banda Aceh and deep interviews with key informants teachers and students. After identifying the application of inquiry and scientific attitudes of students, the development of learning to preserve living things is carried out using developmental analysis related to environmental issues. From observations and interviews the results show that the application of inquiry and scientific attitude of students there is no planning on the learning tools for the preservation of living things, the average value of the percentage of inquiry activities is 29% (low), the average value of the percentage of scientific attitude activities is 61% (moderate), and must be improved through learning to conserve living things. Development of an inquiry syllabus based on scientific attitudes, teaching materials, student activity sheets (LKS), tests of preservation of living things, and attitude scales integrated into targets, principles, and methods in inquiry models based on scientific attitude. Learning to conserve living things with a scientific attitude-based inquiry learning model is expected to be able to build student and community awareness of the preservation of Aceh's forests and the environment in a sustainable manner. Abstrak Kegiatan pelestarian alam bertujuan untuk mempertahankan spesies-spesies tumbuhan dan hewan agar tetap lestari. Upaya untuk melakukan pelestarian alam dapat dilakukan melalui pendidikan. Salah satu strategi yang dapat digunakan sekolah dasar untuk menyadarkan kepedulian siswa terhadap lingkungan melalui pembelajaran pelestarian makhluk hidup dengan menggunakan model pembelajaran inkuiri berbasis sikap ilmiah. Penelitian ini bertujuan untuk mengidentifikasi penerapan inkuiri dan sikap ilmiah siswa dalam pembelajaran pelestarian makhluk hidup melalui analisis kebutuhan, studi dokumentasi, dan studi lapangan. Penelitian ini menggunakan desain Penelitian Kualitatif (Qualitative Research), dilakukan menggunakan metode observasi langsung pada siswa kelas VI semester I yang mengikuti pembelajaran pelestarian makhluk hidup di tiga SD Kota Banda Aceh dan wawancara mendalam (deep interview) dengan informan (key person) guru dan siswa. Setelah mengidentifikasi penerapan inkuiri dan sikap ilmiah siswa maka dilakukan pengembangan pembelajaran pelestarian makhluk hidup menggunakan analisis pengembangan yang berhubungan dengan isu-isu lingkungan. Dari observasi dan wawancara diperoleh hasil bahwa penerapan inkuiri dan sikap ilmiah siswa tidak ada perencanaan pada perangkat pembelajaran pelestarian makhluk hidup, nilai rata-rata persentase aktivitas inkuiri adalah 29% (rendah), nilai rata-rata persentase aktivitas sikap ilmiah adalah 61% (sedang), dan harus ditingkatkan melalui pembelajaran pelestarian makhluk hidup. Pengembangan silabus inkuiri berbasis sikap ilmiah, bahan ajar, lembar kegiatan siswa (LKS), tes pelestarian makhluk hidup, dan skala sikap terintegrasi ke dalam sasaran, prinsip, dan metode dalam model pembelajaran inkuiri berbasis sikap ilmiah. Pembelajaran pelestarian makhluk hidup dengan model pembelajaran inkuiri berbasis sikap ilmiah diharapkan mampu membangun kesadaran siswa dan masyarakat akan pelestarian hutan dan lingkungan Aceh secara berkelanjutan. Kata Kunci: Pembelajaran Pelestarian Makhluk Hidup, Aktivitas Inkuiri, Aktivitas Sikap Ilmiah